The Attack Intensity and Pest Control of Urostylis sp. on Manglid Agroforestry (Magnolia champaca (L.) Baillon ex Pierre - endah suhaendah; Aji Winara (Balai Litbang Teknologi Agroforestry, Ciamis, 2021)
ABSTRACT Development of manglid private forests is experiencing challenges with sucking insects attack of Urostylissp. which inhibits the growth of manglid until death. This study aims to identify the attack percentage and attack intensity of the sucking insects on monoculture, manglid agroforestry, and control efforts. The methods used were exploration and experiment. The results showed that the attack percentage of Urostylis sp. on monoculture and agroforestry patterns were 59% and 53% respectively. Attack intensity of Urostylis sp. on monoculture and agroforestry pattern were 55% and 31% respectively. Pests control using a biological insecticide of 1 g/l Bacillus thuringiensiseffectively caused mortality up to 95% while the botanical insecticide using 5 ml/l Azadirachtin was more effective as a repellant. Pest control of Urostylis sp. using 1 g/l B. thuringiensis can be done during the early dry season.